Effects of Dietary Salt and Boric Acid on Milk Quality in Savak Akkaraman Sheep - Beyazgul, Pelin; Akarsu, Selcukhan; Baykalir, Yasin; Simsek, Ulku Gulcihan (Mdpi, 2026)
This study evaluated the effects of varying dietary salt and boric acid addition doses on the milk quality of Savak Akkaraman sheep. A total of 120 animals were as-signed to six treatment groups (n = 20): control (C), rock salt (S; 10 g/day), boric acid 20 mg/day (B20), boric acid 40 mg/day (B40), BS20 (20 mg boric acid + 10 g/day rock salt), and BS40 (40 mg boric acid + 10 g/day rock salt). All analyses were performed in duplicate on six samples, taken on days 30 and 35 following the administration of the additives. Physicochemical analyses only showed significant variation in milk pH (p = 0.006), while acidity, dry matter, and ash remained unaffected. Strong positive correlations were found among protein, lactose, salt, and density (r > 0.95; p < 0.001). Coagulation times differed widely, with the longest being observed in BS20 (995.03 s) and the shortest in BS40 (141.73 s). Among mineral parameters, only selenium levels differed significantly between the treatment groups (p < 0.05). No significant differences were found for fat, solids-not-fat, lactose, freezing point, or electrical conductivity. Importantly, boron addition had a significant influence on total casein content (p < 0.001). Overall, dietary rock salt and boric acid did not markedly alter the basic milk composition but produced notable physicochemical changes, particularly in coagulation behavior and casein levels, which may influence the technological properties of sheep milk.
Keywords: sheep; milk quality; boric acid; feed additives